Influencing Factors and Exercise Intervention of Cognitive Impairment in Elderly Patients with Chronic Obstructive Pulmonary Disease - Wang T (Dove Medical Press, 2020)
Ting Wang,1 Lijuan Mao,1 Jihong Wang,1 Peijun Li,1 Xiaodan Liu,2,3 Weibing Wu1 1Department of Sports Medicine, Shanghai University of Sport, Shanghai 200438, People’s Republic of China; 2School of Rehabilitation Science, Shanghai University of Traditional Chinese Medicine, Shanghai 201203, People’s Republic of China; 3Institute of Rehabilitation Medicine, Shanghai Academy of Traditional Chinese Medicine, Shanghai 201203, People’s Republic of ChinaCorrespondence: Weibing WuDepartment of Sports Medicine, Shanghai University of Sport, Shanghai 200438, People’s Republic of ChinaTel +86 21 5125 3319Fax +86 21 5125 3380Email wwb75@126.comXiaodan LiuSchool of Rehabilitation Science, Shanghai University of Traditional Chinese Medicine, Shanghai 201203, People’s Republic of ChinaTel +86 15800668700Email hzhp403@126.comAbstract: Chronic obstructive pulmonary disease (COPD) is a common respiratory condition characterized by airflow limitation in the elderly. Airflow limitation is partially reversible and progressive. COPD not only causes a gradual decline in lung function but also affects the function of other systems throughout the body; it also has adverse effects on the central nervous system that can lead to cognitive impairment, especially in elderly patients. Therefore, understanding the influencing factors of cognitive impairment in elderly patients with COPD and applying early intervention are crucial in improving the quality of life of patients and reducing the burden on their families and society. This article mainly discusses the related factors of cognitive impairment in elderly patients with COPD and expands the possible mechanism of exercise in improving cognitive impairment in patients with COPD to provide a reference for the clinical prevention and treatment of cognitive impairment in elderly patients with COPD.Keywords: chronic obstructive pulmonary disease, elderly people, cognitive function, influencing factors, exercise training